Agricultural Production and Climate Change - Kolomieiets, Sofiia; Malá, Ivana, 1962-; Šimpach, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Modern civilisation faces a two-fold challenge regarding food security: ensuring sufficient food supply for the growing population and tackling hunger in the poorest parts of the world. On top of that, climate change is becoming more tangible and poses a potential threat to meeting food security targets in the future. These factors motivated the investigation of agricultural and climatic indicators in this thesis. Specifically, the analysis was focused on the cases of two countries, the Netherlands and Tanzania, which were chosen as representatives of the two tails of the development ladder. The main goal of this thesis is to provide a picture of the past development of agricultural and climatic variables. The thesis can be divided into two parts. In the agricultural part, the focus is on agricultural output growth and the role of productivity. The method of agricultural growth decomposition developed by the USDA is used, and the analysis is performed on the data set of international agricultural indicators published by the USDA. In the second part, two climatic indicators are analysed: average temperatures and total precipitation. The data from ERA5 reanalysis is used for this purpose. Descriptive techniques and methods for time series modelling are used to identify the extent of the changes that occurred over the studied period. The upwards shifts in the temperatures were found in both countries, while precipitation was found to have decreased in Tanzania. The findings in this thesis provide the basis for further research on the relationships between agricultural and climatic variables.
Vedoucí práce: Ivana Malá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: statistické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses